2022
DOI: 10.1007/s13187-022-02216-1
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Oncology Virtual Education Rotation (ROVER) 2.0 for Residents: Implementation and Outcomes

Abstract: The COVID-19 pandemic catalyzed the integration of a virtual education curriculum to support radiation oncologists in training. We report outcomes from Radiation Oncology Virtual Education Rotation (ROVER) 2.0, a supplementary virtual educational curriculum created for radiation oncology residents globally. A prospective cohort of residents completed surveys before and after the live virtual webinar sessions (pre-and post-surveys, respectively). Live sessions were structured as complex gray-zone cases across v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…While many VA-ECHO programs were demonstrating steadily increased engagement over time 15 before 2020, the COVID-19 pandemic resulted in significantly increased interest and participation in virtual education overall. [25][26][27][28] This program provides national access to cancer rehabilitation education, allowing for multidisciplinary VA attendance. This program demonstrates that virtual education plays a valuable role in cancer rehabilitation education, especially in the COVID-19 era where virtual education has risen to supplement in-person events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While many VA-ECHO programs were demonstrating steadily increased engagement over time 15 before 2020, the COVID-19 pandemic resulted in significantly increased interest and participation in virtual education overall. [25][26][27][28] This program provides national access to cancer rehabilitation education, allowing for multidisciplinary VA attendance. This program demonstrates that virtual education plays a valuable role in cancer rehabilitation education, especially in the COVID-19 era where virtual education has risen to supplement in-person events.…”
Section: Discussionmentioning
confidence: 99%
“…While many VA-ECHO programs were demonstrating steadily increased engagement over time 15 before 2020, the COVID-19 pandemic resulted in significantly increased interest and participation in virtual education overall 25–28 . This program provides national access to cancer rehabilitation education, allowing for multidisciplinary VA attendance.…”
Section: Discussionmentioning
confidence: 99%
“… 9 Since this time health care and radiation therapy departments have undergone significant changes, including institutional growth, increase in use of virtual environment following the COVID-19 pandemic, and changes in resident learning techniques. 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 Here, we discuss our institutional experience with chart rounds and the implementation of a new chart rounds application to adapt to modern radiation therapy departmental needs and multiple use scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study assessing the effectiveness of online training for radiation oncologists, Hatcher et al documented the effectiveness of a telehealth brachytherapy training program in increasing the confidence of healthcare professionals in LMICs [15]. Sandhu et al (2022) also reported findings from a multi-institutional case-based radiation oncology virtual education rotation for residents; finding that the sessions significantly increased capacity to treat in majority of participants [16].…”
Section: Introductionmentioning
confidence: 99%